Perencanaan Dana Desa untuk Pengembangan Desa Wisata - Desti Mutia Fatmasari; Priyo Hari Adi (JURNAL ILMIAH EDUNOMIKA, 2021)
This study aims to describe the practice of village funds planning for tourism village development in Sepakung Village. This research uses descriptive qualitative with the type of data used is primary data. Data acquired by interviews and documentation. Qualitive analysis method used data reduction, data presentation, data comparison and conclusion. The results and discussion of this research indicate that the village funds planning for tourism village development in Sepakung Village is well implemented and corresponding with the applicable regulation from Minister of the Interior Regulation Number 114 of 2014 about Village Development Guidelines and Central Java Governor Regulation Number 53 of 2019 about Guide Intruction of Central Java Local Regulation Number 2 of 2019 about Tourism Village Development in Central Java Province. Altough there are difference in the making of RKPDes that little bit slower approximately 1 month than reccomended time by the goverment. Keywords: village fund, tourism, planning